Trying again: repartnering after dissolution of a union - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2002)
The paper uses the first 10 waves of the British Household Panel Survey to study the length of cohabiting unions started in the 1990s, and the time it takes to find a new partner for people who dissolved a marriage or cohabiting union in the 1990s. It finds that the time spent living together in cohabiting unions before either marrying each other or the union dissolving is usually very short. Seventy percent of people leaving a cohabiting union find new partners within five years. This compares with the considerably lower figure of 43% for people leaving a marriage. Older people, whether they have been married or cohabiting, typically repartner more slowly. Repartnering also happens more slowly for widows and widowers, and for individuals who have custody of a child (most of whom are women).
Keywords: 330